Studi Populasi Ikan Beloso (Oxyurichthys microlepis) Di Perairan Morosari Kec. Sayung, Demak - Dian Sari Maisaroh; Sri Rejeki; Muhammad Zainuri (Biotropic : The Journal of Tropical Biology, 2020)
This study aims to study population of beloso fish. The research was conducted between May-June 2010 at Morosari Waters Area, District SayungDemak. Beloso fish catches are measured standard length, total length and weight. The data analysis suchgrowth was using Von Bertalanffy, length - weight relationship, conditional factor and, food and feeding habits.Growthof beloso fish(O. microlepis) in Morosari waters area has a value of L ∞ of 13,49cm by the equation L(t) = 13,49 ( 1 - exp 0,0175 (t-1,9053)) for length,while based on the weight obtained for W ∞ 128,33 grams with the equation W(t) = 128,33 ( 1 - exp -0,003 (t-2,4312))3. Length-weight relationship beloso fish have value of b1,451 in the Morosari waters area. This value indicates that the growth of beloso fish is negative allometric, which the addition of lengthis faster than its weight. Based on data calculations of beloso fish condition factor in the Morosari waters shows the range of condition factors from 0,0965 to 0,3661, which are preferred food energy accretion term. Beloso fish areomnivorous fish that consume phytoplankton, zooplankton, and detritus as food found in the Morosari estuary.